First direct evidence of wild plant grinding process from the Holocene Sahara: Use-wear and plant micro-residue analysis on ground stone tools from the Farafra Oasis, Egypt. (30th July 2020) - Lucarini, Giulio; Radini, Anita
Abstract: The excavation of the 8000-year-old Hidden Valley village has highlighted the importance of wild plant exploitation in the Mid-Holocene contexts of the Farafra Oasis. This site yielded high numbers of plant macro-remains, which were analysed during the early 2000s by A.G. Fahmy. Among these, Sorghum and other species of wild grasses, often found charred in the fireplaces of the site, prevail; together with the assemblage from E−75-6 (Nabta Playa) these represent the oldest evidence of wild Sorghum exploitation in the Eastern Sahara. Hidden Valley village has also yielded one of the largest assemblages of grinding implements for the whole of North Africa, which, until recent times, had been analysed only from a techno-typological perspective. The general assumption of a direct link between grinding tools and plant exploitation has been tested, and challenged using, for the first time for North African contexts, an integrated method, carried out on the actual tools, combining low- and high-power use-wear and plant micro-residue analyses. Firstly, micro-residues (mainly starch granules and phytoliths) were extracted from the Hidden Valley grinding tools, and analysed by means of a high magnification transmitted-light microscope. The identification of the plant micro-fossils was based upon the 'visual matching' of morphological characteristics with those of a purpose-built reference collection of modern starch granules and phytoliths. Then, tool micro-topography and use-wear traces were analysed both using a low- and high-power approach in order to detect the possible presence of macro- and micro-wear associated with plant exploitation. The grinding stones analysed showed very developed wear mainly consistent with plant processing activities. The same artefacts also yielded starch granules, sometimes in large quantities, together with a lower number of phytoliths. A number of plant tribes from the grass family Poaceae were represented in the micro-remain assemblage. Our results integrate and complement the previous archaeobotanical work carried out on the plant macro-remains from this site and stress the important role played by grinding tools in the processing activities of the variety of wild grasses that were consumed as staple food by Eastern Saharan communities during the Holocene.